Kajian Sistem Agribisnis Jeruk Gerga Di Desa Kayu Manis Kecamatan Sindang Kelingi Kabupaten Rejang Lebong - Syaiful Anwar; Febri Nur Pramudya; Gracia Gabrienda (Politeknik Kampar, 2024)
This research aims to determine the agribusiness system for gerga oranges in Kayu Manis Village, Sindang Kelingi District and to determine the income and efficiency of gerga orange farming in Kayu Manis Village, Sindang Kelingi District . The total area of orange plantations in Indonesia is more than 57,000 hectares with a production of 2.5 million tons. The import value in 2019 was 100 thousand tons. The type of Siamese orange/tangerine that has great potential to be used as a superior commodity product is the Gerga orange or Rimau Gerga Lebong (RGL) orange. The limited cultivation locations and advantages they have mean that the price of gerga oranges is still quite high. The selling price currently ranges from IDR 20,000.00 to IDR 30,000.00 per kilogram. One of the villages that has participated in developing RGL gerga orange cultivation and is considered successful is Kayu Manis Village, Sindang Kelingi District. Kayu Manis Village has an average annual farmer income of Rp. 112,617,188/year, while the average total production cost is Rp. 64,119,401, From this figure, the R/C ratio of the Gerga orange farming business is 1.7